Celebrando a Paz e causando Conflitos: as diferentes facetas de Norberto de Xanten - Araujo, Vinicius Cesar Dreger de (Revista Escripturas, 2020)
Norbert of Xanten, founder of the Order of the PremonstratensianRegular Canons (1120) is an exemplary figure both in clerical reforms and in religious effervescence between the 11th and 12th centuries. We will analyze Norbert's performances as a peacemaker in Lotharingia in 1119, as an itinerant preacher and as a cause of conflicts in Magdeburg between 1126 and 1129, already as archbishop in the light of the Spielregln der Politik(by Gerd Althoff) and the Konsensuale Herrschaft(by Bernd Schneidmüller). For this purpose, we will use Vita Norberti Aas ourmain source, complemented when necessary by Vita Norberti B,the Gesta archiepiscoporum magdeburgensiumand the Annales Magdeburgenses.
Keywords: 👤 norbert of xanten

O paradoxo premonstratense após a morte de Norberto de Xanten (1135): vida monástica ou vida canônica? - Araújo, Vinicius Cesar Dreger de (Anais dos Encontros Internacionais de Estudos Medievais, 2019)
Keywords: 📚 premonstratensian (general)

Ermida do Paiva: arquitetura e implantação monástica na serra de Montemuro - Lopes Cunha, Cláudia Gonçalves (Genius Loci: lugares e significados, 2017)
Keywords: ermida do paiva

Ermida do Paiva: Arquitetura e Escultura - Lopes Cunha, Cláudia Gonçalves (University of Porto, 2015)
Keywords: ermida do paiva

Uzos da Igreia da Ermida do Paiva - Carvalhal, Marta; Azevedo, Eufemia (Junta de Freguesia da Ermida, 2013)
Keywords: ermida do paiva

Ermida do Paiva: reflexões e problemáticas - Rosas, Lúcia Maria; Botelho, Maria Leonor; Resende, Nuno (Revista da Faculdade de Letras: Ciências e Técnicas do Património, 2013)
With this article we want to reflect and discuss some of the historical issues concerning the Romanesque architecture, taking as an example the Ermida do Paiva (Castro Daire). Problems like the recovery of medieval heritage, the implantation in the territory or the foundational motivation in Portuguese history context are debated.
Keywords: ermida do paiva